2020
DOI: 10.3390/ma13030730
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Jet Printing of Silver Lines with A High Aspect Ratio on A Heated Silicon Substrate

Abstract: In this work, we studied the formation of conductive silver lines with high aspect ratios (AR = thickness/width) > 0.1 using the modernized method of aerosol jet printing on a heated silicon substrate. The geometric (AR) and electrical (resistivity) parameters of the formed lines were investigated depending on the number of printing layers (1–10 layers) and the temperature of the substrate (25–300 °C). The AR of the lines increased as the number of printing layers and the temperature of the substrate increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…This decrease in w and an increase in the aspect ratio is probably associated with an increase in the contact angle θ as a result of a change in the composition of the nano-ink due to the evaporation of the solvent during the deposition of the nano-ink on a heated substrate. Recently [ 71 , 72 ] it was found that the contact angle can vary over a wide range from 30° to >90° depending on T s and thus largely determine the geometry of the lines being formed. Thus, from the analysis of the optical images of the lines, it was found that the optimal values of T s during the printing process should be about 50–100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in w and an increase in the aspect ratio is probably associated with an increase in the contact angle θ as a result of a change in the composition of the nano-ink due to the evaporation of the solvent during the deposition of the nano-ink on a heated substrate. Recently [ 71 , 72 ] it was found that the contact angle can vary over a wide range from 30° to >90° depending on T s and thus largely determine the geometry of the lines being formed. Thus, from the analysis of the optical images of the lines, it was found that the optimal values of T s during the printing process should be about 50–100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…From the profilometry data, it can be seen that the line heights also increase, which, in particular, leads to an increase in the aspect ratio of the lines. This increase is due to the contact angle between microdroplets, which increases with substrate temperature [37,38]. Thus, it has been found that the optimum value of T s during printing should be in the order of 100 • C. At this substrate temperature, we carried out the experiments to establish the effect of the substrate speed V s and the number of printing layers N p on the width w and homogeneity of the obtained lines.…”
Section: Resultsmentioning
confidence: 99%
“…From the profilometry data, it can be seen that the line heights also increase, which, in particular, leads to an increase in the aspect ratio of the lines. This increase is due to the contact angle between microdroplets, which increases with substrate temperature [ 37 , 38 ]. Thus, it has been found that the optimum value of T s during printing should be in the order of 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, production of germanium nanoparticles with different morphologies, sizes and optical properties by the spark discharge method can be controlled by the temperature of an additional sintering process. This is quite important technology for creating nanoparticles with required properties for applications as anode materials of lithium-ion batteries, sodium-ion batteries [ 35 ] and aerosol jet-printing devices [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%